2019
DOI: 10.29109/gujsc.587637
|View full text |Cite
|
Sign up to set email alerts
|

Toz Metalurjisi Metoduyla Al-SiC Kompozit Malzeme Üretimi ve Aşınma Özelliklerinin Araştırılması

Abstract: In this study, SiC reinforced composite material was produced by applying powder metallurgy production technique as solid state method. Initially, mechanically grinding and mixing process of the aluminum and SiC powder was realized in turbula device containing steel ball. Then, mechanical tests and metallographic examinations of powder metal composite samples which were pressed at 500 MPa pressure and sintered for 2 hours at 650 °C were performed. After the characterization study such as density and hardness m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
5
0
3
Order By: Relevance
“…al., 2020). In composite material production, particle size and the distribution of particles inside the matrix structure are determining parameters on the properties of mechanical of the composite material that is produced (Arık, Kırmızı & Özçatalbaş et al, 2017). The fabrication of MMCs is achieved by both how and cold fabrication methods such as powder metallurgy, die casting, vacuum and pressure infiltration, and hot extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2020). In composite material production, particle size and the distribution of particles inside the matrix structure are determining parameters on the properties of mechanical of the composite material that is produced (Arık, Kırmızı & Özçatalbaş et al, 2017). The fabrication of MMCs is achieved by both how and cold fabrication methods such as powder metallurgy, die casting, vacuum and pressure infiltration, and hot extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…In one of these studies, Arık produced a silicon mat-reinforced composite material with an Al matrix by applying the P/M production method. In his study, he showed that the homogeneous distribution of SiC in the matrix structure was acomplished by mechanical mixing and thus, its mechanical properties were improved [13]. In addition, Şimşek et al investigated microstructural changes and their effect on the wear performance of Al 7075 alloy aged over five different periods and the effect of aging time on wear behavior were revealed.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, unlike other studies [2,[13][14][15], mechanically ground powders were placed in a stainless steel casting chamber and samples were formed by pouring in the molten Al 7075 alloy. Unlike the work done by Aksöz and Bostan, rather than by directly applying the casting process, this study utilized the mechanical properties provided by the grinding to create better hardness and homogeneous distribution properties in the parts produced via P/M [16].…”
Section: Introductionmentioning
confidence: 99%
“…Saf alüminyumun aksine çekme dayanımı, yoğunluk, süneklik, şekillenebilirlik, işlenebilirlik, kaynak kabiliyeti ve korozyon direnci gibi özellikler dikkate alınarak alaşımlı alüminyum üretilmesi ve kullanılması ile birlikte alüminyum matrisli kompozit malzeme üretimi önemli ölçüde artarak devam etmiştir [1,2]. Metal matris kompozitlerde matris malzemesi olarak kullanılan, alüminyum metalinin mekanik özelliklerini iyileştirmek için partikül haldeki Al 2 O 3 [3], SiC [4], Si 3 N 4 [5] B 4 C [6], SiO 2 [7], ZrO 2 [8], WC [9] ve Grafen [10] gibi birçok takviye elamanı kullanılmaktadır [11][12][13][14] Alüminyum alaşımlı takviyeli kompozit malzemelerin mekanik özellikleri genel olarak matrisin özelliğine, ıslanma yeteneğine, takviye oranına ve takviye çapına bağlı olmaktadır [12,13].…”
Section: Introductionunclassified
“…benzinli motorlar için yeni bir silindir bloğu üretmiştir. Bununla birlikte, fren diskleri, %15 Al 2 O 3 takviyeli AA6061 alaşımı tekerlek çivileri, %20 SiC takviyeli Al 9 Si Golf sopası başlığı ve fren kampanaları, alüminyum matrisli kompozit malzemelerden üretilmektedir [11,13]…”
unclassified